Activation of endoplasmic reticulum stress response during the development of ischemic heart disease - Azfer, Asim (2006)
Endoplasmic reticulum (ER) stress has been found to be associated with neurodegenerative diseases and diabetes mellitus. Whether ER stress is involved in the development of heart disease is not known. Cardiac-specific expression of monocyte chemoattractant protein-1 (MCP-1) in mice causes the development of ischemic heart disease. Here we report that microarray analysis of gene expression changes in the heart of these transgenic mice revealed that a cluster of ER stress-related genes was transcriptionally activated in the heart during the development of ischemic heart disease. The gene array results were verified by quantitative real-time PCR that showed highly elevated transcript levels of genes involved in unfolded protein response such as ER and cytoplasmic chaperones, oxidoreductases, protein disulfide isomerase (PDI) family, and ER-associated degradation system such as ubiquitin. Immunoblot analysis confirmed the expression of chaperones, PDI, and ubiquitin. Immunohistochemical analyses showed that ER stress proteins were associated mainly with the degenerating cardiomyocytes. A novel ubiquitin fold modifier (Ufm1) that has not been previously associated with ER stress and not found to be induced under any condition was also found to be upregulated in the hearts of MCP mice (transgenic mice that express MCP-1 specifically in the heart). The present results strongly suggest that activation of ER stress response is involved in the development of ischemic heart disease in this murine model.